Spontaneous Bacterial Peritonitis Caused by Listeria monocytogenes Associated with Ascitic Fluid Lymphocytosis: A Case Report and Review of Current Empiric Therapy. (15th September 2013) - Yecies, Todd; Inagami, Sanae
Abstract : Spontaneous bacterial peritonitis (SBP) is a potentially deadly complication of ascites. We describe a case of SBP caused by Listeria monocytogenes in a patient with alcoholic cirrhosis. This was associated with the unusual finding of ascitic fluid lymphocytosis, which previously had only been associated with tuberculoid or malignant ascites. Given increasing rates of cefotaxime-resistant SBP alongside the possibility of Listeriosis, the use of cefotaxime as first-line therapy in SBP should be reevaluated.